INVESTIGATING THE GAP BETWEEN CUSTOMER EXPECTATION AND EXPERIENCE OF INSTAGRAM USERS IN SURABAYA, INDONESIA - Yovita Angelina; Endo Wijaya Kartika (Jurnal Hospitality dan Manajemen Jasa, 2017)
This study is to investigate the impact of instagram to the expectation and experience of the customer in restaurant in Surabaya, Indonesia. The data produced by using Microsoft excels. It shows what contents that build the customers expectation and how they rate their experiences.  The results show that the contents of instagram that caused and built their content have positive impacts to their experience